AAA Abstract and Applied Analysis 1687-0409 1085-3375 Hindawi Publishing Corporation 10.1155/2015/456364 456364 Research Article On the Equivalence of Differential Equations in the Sense of Coincidence Reflecting Functions Zhou Zhengxin Giné Jaume School of Mathematical Sciences Yangzhou University Yangzhou 225002 China yzu.edu.cn 2015 2842015 2015 07 03 2015 17 04 2015 20 04 2015 2842015 2015 Copyright © 2015 Zhengxin Zhou. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

We use a new method for constructing some differential equations which are equivalent to a given equation in the sense of having the same reflecting function. We completely solve the problem: when is a polynomial differential equation equivalent to a given polynomial differential equation? Many sufficient conditions have been established for one differential equation to be equivalent to a given differential equation. We apply the obtained results to study the boundary value problem of two equivalent differential equations.

1. Introduction

By [1, 2] we know that some polynomial differential system(1)u˙=Uu,v,v˙=Vu,v,where U(u,v) and V(u,v) are polynomial functions, can be transformed to an equation of the form(2)dxdt=p0t+p1tx++pntxn=Pt,x,t,xR,where pi(t) are polynomial in cost, sint. The fact that systems with a homogeneous nonlinearity can be transformed to (2) with n=3 has been exploited in a number of previous papers . The limit cycles of (1) correspond to 2π-periodic solutions of (2). This fact has been used to facilitate certain computations and to provide some information about the global phase portrait of the system. In this paper we will use the method of Mironenko  to construct some differential equations which are equivalent to (2) in the sense of having the same reflecting function.

Now, we simply introduce the concept of the reflecting function.

Consider differential system(3)x=Xt,x,tR,xDRn,which has a continuously differentiable right-hand side and general solution φ(t;t0,x0). For each such system, the reflecting function is defined as F(t,x)φ(-t,t,x) .

If system (3) is 2π-periodic with respect to t, then TxF-π,x is the Poincaré mapping of (3) over the period [-π,π]. Thus, the solution x=φ(t;-π,x0) of (3) defined on [-π,π] is 2π-periodic if and only if x0 is a fixed point of T(x).

A differentiable function F(t,x) is a reflecting function of system (3) if and only if it is a solution of the Cauchy problem(4)Ftt,x+Fxt,xXt,x+X-t,Ft,x=0,F0,x=x.

If the reflecting functions of two differential systems coincide in their common domain, then these systems are said to be equivalent .

If F(t,x) is the reflecting function of (3), then it is also the reflecting function of any system(5)x=Xt,x+Fx-1Rt,x-R-t,Ft,x,where R(t,x) is an arbitrary vector function such that the solutions of every system above are uniquely determined by its initial conditions. The systems (3) and (5) have the same operators of translation along solutions on the symmetric time interval [-ω,ω], and therefore the initial data x(-ω) of solutions of the boundary value problems of the form Φ(x(ω),x(-ω))=0, where Φ is an arbitrary function, coincide for such systems.

In general, it is very difficult to find out the reflecting function of (3), so to writ out system (5) is difficult, too. How to judge if two systems are equivalent when we do not know their reflecting function? This is a very interesting problem! Mironenko in  has studied it and obtained some good results.

Lemma 1 (see [<xref ref-type="bibr" rid="B6">6</xref>]).

If continuously differentiable vector functions Δi(t,x)(i=1,2,,m) are solutions of differential system(6)Δtt,x+Δxt,xXt,x=Xxt,xΔt,x,then all perturbed systems of the form(7)x=Xt,x+i=1mαitΔit,x,where αi(t) are arbitrary continuous scalar odd functions, are equivalent to each other and to system (3).

The theory of reflecting function has been used for studying the qualitative behavior of solutions of differential systems by many authors .

Now, for a given equation (2), we present a method for constructing other first-order differential equations which are equivalent to (2), that is, to find out the solution of (6) with X(t,x)=P(t,x). However, it is impossible to find all the solutions in most cases. Therefore, we take only polynomial solutions of (6), that is, its solutions of the form(8)Δ=a0t+a1tx++antxn,where the coefficients ai(t)(i=0,1,2,,n) are assumed to be differentiable functions on R and an(t) is not to be zero identically.

Bel’skii in papers  has discussed, respectively, when a first-order polynomial differential equation is equivalent to a linear equation (n=1) and Riccati equation (n=2) and Abel equation (n=3). In this paper, we will in detail discuss when is a first-order equation equivalent to (2) with n3. We have obtained the sufficient conditions for (6) has solution in form of (8) and we give the explicit expressions of Δ(t,x). At the same time, in addition, we also find out some nonpolynomial solutions of (6). The results of this paper generalize the results of Bel’skii , and the method of proof in this paper is more simple and efficient than in the previous papers.

2. Main Results

Now, we consider (2) and assume that pn(t) is not to be zero identically in R and n>1. By Bel’skii , we know that if pn0, then the degree of polynomial Δ(t,x) is equal to n. In the following, we suppose that n3 and pn(t)0.

Theorem 2.

For (2), suppose that n3 and pn(t)0. Then the function Δ(t,x) of the form (8) is a solution of (6), if and only if(9)a0=p1a0-a1p0,(10)ak=k+1pk+1a0-ak+1p0+k-1pka1-p1ak,k=1,2,,n-2,(11)ai=pipnan,i=2,3,,n-1,(12)a1=p1pnan+ann-1pn,(13)a0=p0pnan+annpnpn-1pn+anpn-1nn-1pn2.Therefore, Δ can be represented in the form(14)Δ=anpnPt,x+ann-1pnx+pn-1npn+annpnpn-1pn.

Proof.

Let us substitute the function Δ(t,x) of the form (8) into (6); we get(15)a0+a1x++anxn+a1+2a2x++nanxn-1·p0+p1x++pnxn=p1+2p2x++npnxn-1·a0+a1x++anxn.Equating the coefficients of the like power of x, we obtain(16)ak=i=1k+1ipiak+1-i-aipk+1-i,k=0,1,2,,2n-1,where ak=0 and pk=0, when k>n.

From (16) when k=2n-1 we get nanpn=npnan. Taking k=2n-2 in (16), we have an-1=(pn-1/pn)an. Similarly for k=2n-3, 2n-4,,n+1, we get(17)ai=pipnan,i=2,3,,n-1;that is, relation (11) is true.

Substituting (11) into (16) and simplifying we get (10).

Using relation (11) and taking k=n in (16), we get(18)an=n-1a1pn-p1an;it implies relation (12).

Using relation (12) and taking k=n-1 in (16), we have(19)an-1=npna0-p0an+n-2n-1pn-1pnan;substituting an-1=(pn-1/pn)an into the above, we get that relation (13) is held.

Substituting (11)–(13) into (8), we get(20)Δt,x=anpnp0+p1x++pnxn+ann-1pnx+pn-1npn+annpnpn-1pn=anpnPt,x+ann-1pnx+pn-1npn+annpnpn-1pn,which completes the proof.

We rewrite P(t,x) as follows:(21)Pt,x=pnx+pn-1npnn+δn-2x+pn-1npnn-2++δ1x+pn-1npn+δ0,in which(22)δk=1k!pnkPt,xxkx=-pn-1/npn,k=0,1,,n-2,δn-10.

Lemma 3.

If δi=0, i=k+1,k+2,,n-2, k0, then(23)δk=pkpn-Cnkpn-1npnn-k,(24)pk+1pn=Cnk+1pn-1npnn-k-1.

Proof.

As δi=0, i=k+1,k+2,,n-1, so (21) goes to(25)Pt,xpn=x+pn-1npnn+δkx+pn-1npnk+δk-1x+pn-1npnk-1++δ0,equating the coefficients of xk and xk+1; from here we get relations (23) and (24).

Theorem 4.

Suppose that δi=0, i=k+1,k+2,,n-2, δk0(1<k<n-1), and(26)m+1pm+1μk0+m-1pmμk1=pmpn-n-1n-kpmpnδkδk,m=2,3,,k-1,(27)a0=p1a0-a1p0,(28)a1=2p2a0-2p0a2,(29)am=pmpnan,m=2,3,,n-1,where(30)μk0=1npnpn-1pn-pn-1nn-kpn2δkδk,μk1=-δkn-kpnδk,(31)a0=p0pnan+μk0an,(32)a1=p1pnan+μk1an,(33)an=δk-n-1/n-k.Then the function Δ(t,x) in (8) is a solution of (6); that is, (2) is equivalent to equation(34)x=Pt,x+αtΔt,x,where α(t) is an arbitrary continuous odd function.

Proof.

For kmn-2, by Lemma 3, substituting (12) and (13) into (10), we obtain(35)am=m+1pm+1a0-am+1p0+m-1pma1-amp1=m+1pm+1npnpn-1pnan+pm+1nn-1pn-1pn2an+m-1pmann-1pn.Substituting (24) into this relation, we obtain(36)am=m+1n-mCnm+1pn-1npnn-man+m+1n-1Cnm+1pn-1npnn-man+m-1n-1pmpnan.By (11) and (23), we get(37)anδm+n-mn-1δman=0.As δm=0(m=k+1,k+2,,n-1), (37) is an identity when m=k+1,k+2,,n-1. For m=k, solving (37), we have(38)an=δk-n-1/n-k.Substituting (38) into (11)–(13), we obtain (29)–(32).

On the other hand, by relation (10), for 1<m<k, we have(39)am=m+1pm+1a0-am+1p0+m-1pma1-amp1.Substituting (29)–(32) and (37) into the above, we obtain(40)pmpnan-n-1n-kpmanδkpnδk=m+1pm+1μk0an+m-1pmμk1an,which deduces that relation (26) is true. By Theorem 2 and in (10) taking k=1 we get that relations (27) and (28) are held.

By Lemma 1 and Theorem 2, the proof is completed.

Theorem 5.

Supposing that n>3,(41)δi=0,i=2,3,,n-2,δ1=p1pn-Cn1pn-1npnn-10,ηan+nn-1ηan=0,ak=pkpnan,k=2,3,,n-1(42)a0=p0pn-pn-1δ1npn+1npnpn-1pnan+λ0pn-1npn,(43)a1=npn-1npnn-1an+λ0,where(44)ηp0pn-pn-1npnn+1pnpn-1npn-pn-1npnδ1,(45)an=e-n-1δ1pndtλ1+λ0n-1pnen-1δ1pndtdt,where λ0 and λ1 are arbitrary constants. Then the function Δ(t,x) of the form (8) is a solution of (6); that is, (2) is equivalent to (34).

Proof.

As δm=0, m=2,3,,n-1 and δ10, by Lemma 3, we have(46)δ1=p1pn-Cn1pn-1npnn-1,p2pn=Cn2pn-1npnn-2.Using δm=0(m=2,3,,n-1), it is not difficult to check that (37) is an identity when m=2,3,,n-2. For m=1, in relation (10) taking k=1 and computing, it follows that(47)a1=nanpn-1npnn-1,which implies that(48)a1=npn-1npnn-1an+λ0.Combining relation (12), it yields(49)an=-n-1δ1pnan+n-1λ0pn;solving this equation we get the expression (45).

Substituting (49) into (13) implies (42). Substituting (42)–(45) into equation a0=p1a0-p0a1 and simplifying we get ηan+(n/(n-1))ηan=0. By Theorem 2, the proof is finished.

Similarly, we get the following.

Theorem 6.

Supposing that δm=0, m=1,2,,n-2 and δ0=p0/pn-(pn-1/npn)n0,(50)δ0+1npnpn-1pnan+nn-1anδ0+1npnpn-1pn=0,ak=pkpnan,k=2,3,,n-1,a0=p0pnan+annpnpn-1pn+pn-1npnλ0,a1=p1pnan+λ0,where(51)an=n-1λ0pndt+λ1;λ0 and λ1 are arbitrary constants. Then (2) is equivalent to (34).

Theorem 7.

Supposing that δm=0, m=0,1,2,,n-2,(52)anpn-1pn+λ0pn-1=λ2npn,a0=p0pnan+λ2,a1=p1pnan+λ0,ak=pkpnan,k=2,3,,n-1,where (53)an=n-1λ0pndt+λ1;λi(i=0,1,2) are arbitrary constants. Then (2) is equivalent to (34).

By the literature , we know the following.

Corollary 8.

If all the conditions of one of the above four theorems (Theorems 47) are satisfied and (2) is 2π-periodic in t, then the initial data x(-π) of solutions of the boundary value problems of the form Φ(x(π),x(-π))=0, where Φ is an arbitrary function, coincide for systems (2) and (34).

Example 9.

The equation(54)x=x-sint4+costhas the only one 2π-periodic solution x=sint. For this equation, we have(55)p0=cost+sin4t,p1=-4sin3t,p2=6sin2t,p3=-4sint,p4=1,δ3=δ2=δ1=0,δ0=cost.By Theorem 6, we get(56)a4=3λ0t+λ1,where λ0 and λ1 are constants:(57)a3=-4a4sint,a2=6a4sin2t,a1=-4a4sin3t+λ0,a0=a4sin4t-λ0sint.As(58)δ0+14p4p3p4=cost-cost=0,then(59)δ0+14p4p3p4a4+43a4δ0+14p4p3p4=0;that is, the first condition of Theorem 6 is satisfied. Thus(60)Δ0=3λ0t+λ1x-sint4+λ0x-sint.Taking λ0=0 and λ1=1, we get(61)Δ1=x-sint4.Taking λ0=1 and λ1=0, we have(62)Δ2=3tx-sint4+x-sint.Therefore, (54) is equivalent to equation(63)x=x-sint4+cost+α0tΔ0+α1tΔ1+α2tΔ2,where αi(t)(i=0,1,2) are arbitrary continuously odd functions. By Corollary 8, (63) has only one solution such that x(-π)=x(π).

Now, taking n=3 in the above theorems, we get the following corollaries.

Corollary 10.

Suppose that p30; then(64)ζa3+32ζa3=0,ζp0p3-p23p33+1p3p23p3-p23p3σ1,a0=p0p3-p23p3σ1a3+a33p3p2p3+p23p3λ0,a1=p223p32a3+λ0,a2=p2p3a3,where(65)a3=e-2σ1p3dtλ1+2λ0p3e2a3σ1dtdt;λ0 and λ1 are arbitrary constants; σ1=p1/p3-p22/3p32. Then the Abel equation(66)x=p0+p1x+p2x2+p3x3is equivalent to equation(67)x=p0+p1x+p2x2+p3x3+αta0+a1x+a2x2+a3x3,where α(t) is an arbitrary continuously odd function.

Corollary 11.

Suppose that p30, σ1=p1/p3-p22/3p32=0, and σ0=p0/p3-p23/27p330;(68)σ0+13p3p2p3a3+32a3σ0+13p3p2p3=0,a0=p0p3a3+a33p3p2p3+p23p3λ0,a1=p1p3a3+λ0,a2=p2p3a3,where(69)a3=2λ0p3dt+λ1;λ0 and λ1 are arbitrary constants. Then Abel equation (66) is equivalent to (67).

Corollary 12.

Suppose that p30, σ1=p1/p3-p22/3p32=0, and σ0=p0/p3-p23/27p33=0;(70)a3p2p3+λ0p2=3λ2p3,a0=p0p3a3+λ2,a1=p1p3a3+λ0,a2=p2p3a3,where(71)a3=2λ0p3dt+λ1;λi(i=0,1,2) are arbitrary constants. Then Abel equation (66) is equivalent to (67).

Example 13.

Abel equation(72)x=x3+6x2+3x-10=x+23-9x+2has three constant solutions x1(t)=-2, x2(t)=-5, and x3(t)=1. For this equation, we have p0=-10, p1=3, p2=6, p3=1, and σ1=-9.

Thus(73)ζ=p0p3-p23p33+1p3p23p3-p23p3σ1=-18+18=0,and ζa3+(3/2)ζa3=0.

Solving a3=18a3+2λ0, we get(74)a3=λ1e18t-19λ0,where λ0, λ1 are arbitrary constants. Therefore(75)a1=3λ1e18t-19λ0+9λ1e18t,a0=-10λ1e18t-19λ0+18λ1e18t,Δ0=λ1e18t-19λ0x3+6x2+3x-10+9λ1e18tx+2.Taking λ1=0 and λ1=-9, we obtain(76)Δ1=x3+6x2+3x-10.Taking λ0=0 and λ1=1, we get(77)Δ2=e18tx3+6x2+12x+8.Consequently, by Lemma 1 and Corollary 10, Abel equation (72) is equivalent to equation(78)x=x3+6x2+3x-10+α0tΔ0+α1tΔ1+α2tΔ2,where αi(t)(i=0,1,2) are arbitrary continuously odd functions. By Corollary 8, (78) has only three solutions such that x(-a)=x(a) (a is a nonzero constant).

Remark 14.

The conclusions of the above three corollaries have been proven by Bel’skii and Mironenko in .

Because (6) is a linear equation, if Δi(i=1,2,,m) are solutions of (6), then Δ=i=1mCiΔi also is solution of (6), where Ci(i=1,2,,m) are arbitrary constants. In the following, we will find out some solutions Δi of (6) in the other form.

Theorem 15.

For the first-order differential equation x=X(t,x)(t,xR), if Δi(i=1,2,,m) are solutions of (6), then Δ=Δk1Δk2Δkm, i=1mki=1, is a solution of (6), too.

Proof.

As(79)Δit+ΔixXt,x-XxΔi=0,i=1,2,,mand k1+k2++km=1,(80)Δt+ΔxXt,x-XxΔ=k1Δ1k1-1Δ2k2ΔmkmΔ1t+Δ1xXt,x-XxΔ1+k2Δ1k1Δ2k2-1ΔmkmΔ2t+Δ2xXt,x-XxΔ2++kmΔ1k1Δ2k2Δmkm-1Δmt+ΔmxXt,x-XxΔm=0.

Thus, the proof is completed.

By Example 9 and Theorem 15 we get that equation(81)x=x-sint4+costis also equivalent to equation(82)x=x-sint4+cost+i=1mαitΔ0ki0Δ1ki1Δ21-ki0-ki1,where αi(t)(i=1,2,,m) are arbitrary continuously odd functions, ki0, ki1 are arbitrary constants, and Δi(i=0,1,2) are the same as in Example 9. This equation has only one solution such that x(-π)=x(π).

Using Theorem 15 and Corollary 10 we get the following.

Corollary 16.

Supposing that p30,(83)ζp0p3-p23p33+1p3p23p3-p23p3σ1=0.Then Abel equation(84)x=p0+p1x+p2x2+p3x3is equivalent to equation(85)x=p0+p1x+p2x2+p3x3+α1Δ+α2Δ1+α3Δ2+α4Δ1kΔ21-k,where αi(t)(i=1,2,3,4) are arbitrary continuously odd functions and k is a constant:(86)Δ=a0+a1x+a2x2+a3x3,in which(87)a0=p0p3-p23p3σ1a3+a33p3p2p3+p23p3λ0,a1=p223p32a3+λ0,a2=p2p3a3,a3=e-2σ1p3dtλ1+2λ0p3e2a3σ1dtdt;λ0, λ1 are arbitrary constants, and σ1=p1/p3-p22/3p32. Consider(88)Δi=a0i+a1ix+a2ix2+a3ix3,i=1,2aj1=ajλ0=1,λ1=0,aj2=ajλ0=0,λ1=1,j=0,1,2,3.

Theorem 17.

For equation(89)x=βtfx,t,xR,fx0,(90)Δ=fxϕ1fxdx-βtdtis a solution of (6). Thus, (89) is equivalent to equation(91)x=βtfx+αtΔt,x,where α(t) is an arbitrary continuously odd function, ϕ(u) is an arbitrary differentiable function, and β(t) is a continuous function.

This result is easy to be proven.

Obviously, from Theorem 17, we see that if f(x) is a polynomial of x, then the corresponding equation (6) has at least one polynomial solution Δ=f(x). This is implied by taking ϕ(u)=1 in (90).

By Theorem 17, (72) is also equivalent to(92)x=x3+6x2+3x-10·1+αtϕx+22-9x+22e-18t.If in (92) we put ϕ(u)=1/(1+u2), then we obtain(93)x=x3+6x2+3x-10·1+αtx+24e36tx+24e36t+x+22-92,where α(t) is an arbitrary continuously odd function. This equation has only three solutions such that x(-a)=x(a) (a is a nonzero constant).

Conflict of Interests

The author declares that there is no conflict of interests regarding the publication of this paper.

Acknowledgments

The work was supported by the NSF of Jiangsu of China under Grant no. BK2012682 and the NSF of China under Grant nos. 11271026 and 61374010.

Devlin J. Lloyd N. G. Pearson J. M. Cubic systems and Abel equations Journal of Differential Equations 1998 147 2 435 454 MR1633961 2-s2.0-0000829449 10.1006/jdeq.1998.3420 Cherkas L. A. On the number of limit cycles of an autonomous second-order system Differential Equations 1976 12 944 946 Neto A. L. On the number of solutions of the equations dx/dt  =j=0naj(t)xj, 0 t1; for which x0=x1 Inventiones Mathematicae 1980 59 67 76 Lijun Y. Yuan T. Some new results on Abel equations Journal of Mathematical Analysis and Applications 2001 261 1 100 112 10.1006/jmaa.2001.7478 MR1850959 2-s2.0-0035457380 Mironenko V. I. Analysis of Reflective Function and Multivariate Differential System 2004 Gomel, Belarus University Press Mironenko V. V. Time-symmetry-preserving perturbations of differential systems Differential Equations 2004 40 10 1395 1403 10.1007/s10625-005-0064-y MR2200005 Mironenko V. I. Mironenko V. V. Time symmetries and in-period transformations Applied Mathematics Letters 2011 24 10 1721 1723 10.1016/j.aml.2011.04.027 MR2803013 2-s2.0-79957551094 Bel’skii V. A. On the construction of first-order polynomial differential equations equivalent to a given equation in the sense of having the same reflective function Differential Equations 2012 48 1 13 20 10.1134/s0012266112010028 MR2963237 2-s2.0-84857812646 Bel’skii V. A. Mironenko V. I. Reflecting function preserving polynomial perturbations of Abel equation Problems of Physics, Mathematics and Technics 2011 9 4 79 85 Bel’skii V. A. Mironenko V. I. Constructing of Abel equation equivalent to the equation of the form x=Atξ0+ξ1x+ξ2x2+ξ3x3 Problems of Physics, Mathematics and Technics 2012 11 2 55 61 Musafirov E. V. Differential systems, the mapping over period for which is represented by a product of three exponential matrixes Journal of Mathematical Analysis and Applications 2007 329 1 647 654 10.1016/j.jmaa.2006.06.085 MR2306829 2-s2.0-33846310413 Maiorovskaya S. V. Quadratic systems with a linear reflecting function Differential Equations 2009 45 2 271 273 10.1134/s0012266109020153 MR2596738 2-s2.0-63749083400 Zhou Z. X. On the Poincaré mapping and periodic solutions of nonautonomous differential systems Communications on Pure and Applied Analysis 2007 6 2 541 547 2-s2.0-34248212349 10.3934/cpaa.2007.6.541 MR2289838